Cartas de Luis Muñoz Rivera a Roberto H. Todd - Todd, Roberto H.; Muñoz Rivera, Luis (My University, 1910)
Envio a Roberto H. Todd del "Congressional Record"
Keywords: United States. Congress. House.; Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.